2022
DOI: 10.3389/fphys.2022.828020
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Inhibited P2X7 Purinergic Receptors to Improve Cardiac Remodeling in Mice With Type 2 Diabetes

Abstract: Background: Diabetic cardiomyopathy (DCM), the main complication of diabetes mellitus, presents as cardiac dysfunction by ventricular remodeling. In addition, the inhibition of P2X7 purinergic receptors (P2X7R) alleviates cardiac fibrosis and apoptosis in Type 1 diabetes. However, whether exercise training improves cardiac remodeling by regulating P2X7R remains unknown.Methods: Db/db mice spontaneously induced with type 2 diabetes and high-fat diet (HFD) and mice with streptozotocin (STZ)-induced type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Besides improving diastolic dysfunction, MIT also normalized systolic function by significantly increasing EF and FS in the WD-fed rats. In line with our findings, an increased EF and FS were observed following 8 weeks and 12 weeks of MIT in HFD and STZ-induced rats and mice, respectively [ 84 , 85 ]. Furthermore, 8 weeks of HIIT has been demonstrated to only improve diastolic function (i.e., the ratio of peak mitral flow velocity versus peak mitral annular velocity (e/e’)), whereas systolic function (i.e., FS and EF) remained unchanged in HFD-induced diabetic mice [ 72 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Besides improving diastolic dysfunction, MIT also normalized systolic function by significantly increasing EF and FS in the WD-fed rats. In line with our findings, an increased EF and FS were observed following 8 weeks and 12 weeks of MIT in HFD and STZ-induced rats and mice, respectively [ 84 , 85 ]. Furthermore, 8 weeks of HIIT has been demonstrated to only improve diastolic function (i.e., the ratio of peak mitral flow velocity versus peak mitral annular velocity (e/e’)), whereas systolic function (i.e., FS and EF) remained unchanged in HFD-induced diabetic mice [ 72 ].…”
Section: Discussionsupporting
confidence: 91%
“…Three studies have previously indicated that HIIT potentially induced physiological cardiac hypertrophy or a so-called athlete’s heart, assessed as increased heart weight and size and improved cardiac function, in HFD-induced T2DM mice [ 72 , 78 , 83 ]. Additionally, three studies on HFD-induced T2DM mice reported no changes in heart weight [ 77 ] or PWT [ 84 , 85 ] following MIT, suggesting the absence of physiological hypertrophic effects. Here, we are the first to show a decreased heart weight and PWT following both MIT and HIIT in high-sucrose diet-induced diabetic cardiomyopathy, potentially indicating the therapeutic nature of endurance exercise training against pathological cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of collagen deposition was determined by Masson's trichrome (G1340, Solarbio, China) or Sirius Red staining (G1472, Solarbio, China). An anti-4-hydroxynonenal antibody (MAB3249, R&D Systems) was used for immunohistochemical staining of heart sections according to our previously described procedures [ 20 ]. The pathological sections were imaged using an upright microscope (400 × magnification; Leica, Germany) and subsequently subjected to histopathological evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent studies in DCM mice have demonstrated that although exercise has a limited impact on interstitial fibrosis, it can effectively reverse cardiac dysfunction by reducing the activity of NLRP3 inflammasome and inhibiting pyroptosis (Takahashi, 2019;Zhang et al, 2019). Moreover, in DCM rat models, elevated expression levels of the P2X7 receptor, NLRP3, caspase-1, and serum IL-1β were observed in the myocardium (Wang et al, 2022). However, following a 12-week treadmill running regimen in these rats, improvements were observed in terms of collagen deposition, cell disorder, as well as the expression levels of NLRP3, caspase-1, P2X7 receptor, and IL-1β within their heart (Zhang et al, 2015).…”
Section: Exercise Improves Dcm and Inhibits Nlrp3 Inflammasomementioning
confidence: 99%